Lessons learned from implementing project management games - David Rumeser; Margaret Emsley (Serious Games Society, 2019)
The purpose of this paper is to identify the principles governing successful project management serious (educational) game design and implementation by identifying lessons learned from implementing such games. This paper applied a triangulation method that qualitatively blends the perspectives of project management practitioners, game designers, and learners. The findings of this paper suggest principles of game realism, context, display, gameplay clarity, target audience, feedback, setting, debriefing, communication mode, and personalization. The main potential beneficiaries of this research include project management educators, trainers, students, training participants, and game designers. The study provides a comprehensive project management game design and implementation guideline that could help improve the quality of project management serious games. This paper is the first exploratory study to blend the perspectives of learners (students), serious game experts, and experienced project management practitioners in order to identify the key principles of delivering successful project management educational or serious games.